Karst Geotourism in Miné-Akiyoshidai Karst Plateau - Koji Wakita; Hokuto Obara (Badan Pelaksana Rinjani-geopark Rinjani Lombok, 2023)
Miné-Akiyoshidai Karst Plateau Geopark is a National Geopark in Japan, aiming to become a UNESCO Global Geopark. Late Paleozoic limestone is the most important geological heritage in this geopark. This limestone originates from a coral reef formed at the top of a submarine volcano born in Early Carboniferous. Due to oceanic plate movements, it continued to move for about 80 million years and arrived at the trench near Japan in middle Permian. The coral reef was detached from the volcano and was accreted into Eastern Asian continental margin. This limestone emerged on the surface of the earth due to the ascent and scraping of the continental margins and now forms the karst plateau. On the surface of the earth, there is a beautiful karst plateau where a semi-natural grassland is maintained by the annual mountain-burning. There are more than 400 limestone caves underground, three of which are open to tourists at all times. The main geotourism activity is a guided geotour of the karst plateau. At the Geopark Center, several trained geoguides are waiting to guide you through the beautiful scenery while explaining the origins of the karst plateau and limestone caves according to the needs of tourists. For small numbers of wealthy tourists, underground lake exploration geotours are available, supported by experts trained in cave exploration. Universally accessible tourism is a form of travel designed for everyone to be able to enjoy it, with the goal of enabling everyone to participate without hesitation, even people of advanced age or people with disabilities. We conducted a special wheelchair operation training, and in 2021 we conducted a geotour where people with disabilities who cannot move from the neck down can enjoy the limestone cave despite many ups and downs and stairs.